The United States Grinnell expedition in search of Sir John Franklin. : A personal narrative. - Kane, Elisha Kent, 1820-1857. (New York : Sheldon, Blakeman & Co.; Philadelphia : Childs & Peterson, 1857)
Spine title: Arctic explorations, first expedition. Mode of access: Internet.